4-Octyl itaconate treatment inhibits mitochondrial dysfunction and ER stress via stimulating SIRT1 expression in vitro and attenuates osteoarthritis process in murine DMM model in vivo - Ziping Yu; Zhao Zhang; Xuancheng Zhang; Junduo Bao; Hualin Li; Jiapei Yu; Ning Shi; Fulong Nan; Liang Cao; Chenghui Li; Wei Wang (Journal of Functional Foods, 2023)
Osteoarthritis (OA), a degenerative disease, has many pathological factors, including oxidative stress (OS), endoplasmic reticulum (ER) stress, apoptosis, and extracellular matrix (ECM) degeneration. OS regulates the pathological progression of OA via mitochondrial dysfunction, and ER stress and by modulating the derivation and elimination of reactive oxygen species (ROS). Though. 4-octyl itaconate (4-OI) is known for its effects on the treatment of various diseases, how it affects OA and its underlying mechanism still needs to be elucidated. Therefore, it is necessary to explore the effects of 4-OI both in vivo and in vitro. In our study, we used H2O2, which can accumulate ROS, OS and ER stress, to imitate the OA model in vitro. Using western blot, real-time quantitative reverse transcription polymerase chain reaction and immunofluorescence staining, we found that 125 μM 4-OI can inhibit apoptosis, ECM degeneration, mitochondrial dysfunction, ER stress and abundant accumulation of ROS in chondrocytes. We also showed that 4-OI can activate the Sirtuin1 gene (SIRT1). We used a SIRT1 inhibitor EX527 to identify the relationships among these pathological factors, and it showed that the 4-OI-mediated effect was achieved by promoting the SIRT1. In vivo, the bilateral medial meniscus was resected to establish the destabilization of the medial meniscus model wherein intraperitoneal injections of 2% and 5% 4-OI postponed the progression of OA. Collectively, this study confirmed that 4-OI can potentially impede the progression of OA by promoting the expression of SIRT1.